Quiet Eye supports winner shots in a simulated table tennis competition - Vincze, A.; Iliescu, D.; Jurchis, R. (Scandinavian Journal of Medicine & Science in Sports, 2022)
Background QE is defined as the final fixation on a specific location or object in the visuomotor workspace, for a minimum of 100 ms, that enables the athletes to gather relevant information before a critical movement. Several lines of research indicate that QE contributes to sports performance. However, its contribution to performance is derived mainly from research investigating isolated motor tasks. Therefore, little is known about its contribution in realistic competitional settings.